Evaluasi keaslian Gereja Protestan di Indonesia bagian Barat (GPIB) Immanuel (Gereja Merah) Kota Kediri berdasarkan Nara grid - Yusfan Adeputera Yusran; Sebastian Hadinata (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Evaluation the authenticity of Gereja Protestan di Indonesia bagian Barat (GPIB) Immanuel (Red Church) in Kediri City using the Nara grid The Dutch Indies buildings still exist in Indonesia. The buildings have historical values and valuable architectural aspects. One of the buildings is GPIB Immanuel or also known as “Gereja Merah” (the Red Church) in the City of Kediri. This study aims to evaluate the authenticity of this building. Nara grid was used as the instrument of assessment. The mix of qualitative and quantitative method was applied to analyze visual, spatial and structural aspects and dimensions of the building. These aspects were described with the Nara grid. To ensure the result of analysis, questionnaires were distributed to society. The result of the analysis shows that though the building has been renovated, its authenticity values remain and are encouraged to be preserved. © 2019 Sebastian Hadinata, Yusfan Adeputera Yusran